Experiments, Policy, and Theory in Development Economics : A Response to Glenn Harrison’s 'Field Experiments and Methodological Intolerance' - Bossuroy, Thomas (Taylor and Francis, 2016)
In ‘Field Experiments and Methodological Intolerance,’ Glenn Harrison develops a criticism of randomized field experiments and denounces ‘intolerance’ for lab experiments and a ‘disconnect from theory.’ We argue that (i) lab experiments and RCTs are based on different methodological approaches and therefore fulfill different scientific objectives; (ii) key features of the RCT methodology make it highly relevant for policy-making, which accounts for a large part of its uptake; (iii) RCTs foster a convergence of interests between policy-makers and researchers around the study of economic mechanisms, which makes it possible to challenge and improve economic theory based on real-world facts; and (iv) hybrid forms of experimentation are being increasingly used and open promising avenues. In sum, economic research based on RCTs is more and more connected to theory and other forms of experiment, while also helping policy-makers tackle daunting problems of poverty and exclusion.